Estudio técnico-económico para la implementación de material didáctico para el laboratorio de automatismos II de la Carrera de Ingeniería Eléctrica de la Universidad Politécnica Salesiana Campus Kennedy Torres Marmol. - Torres Marmol, Diego Javier (2009)
The second chapter is about the development of the laboratory Practice, they are eighteen; each one has five parts, Objectives, General Information, Preparatory Job, Laboratory and Investigation. General information is the basic theory necessary about the Practice. The Preparatory Job has questions o requirements necessaries for complete the practice. The Laboratory is based in the experimentation, using the observation and taking values. In the investigation you have to analyze and make conclusions, also complete the knowledge with extra information without experiment.